Fracture resistance and marginal fit of three different overlay designs using advanced zirconia-reinforced lithium disilicate CAD/CAM material - Heidi Saad Refaey; Sanaa H. Abdelkader; Yasser M. Aly (BMC Oral Health)
Abstract Background Conservative dentistry introduced modern restoration designs, contributing to the greater use of partial-coverage ceramic restorations. New strong bondable ceramic materials made fabricating partial coverage ceramic restorations easier to restore the badly destructed teeth. Aim of the study This study investigated the impact of three distinct overlay preparation designs on the marginal fit (both before and after thermal aging) and the fracture resistance of overlay restorations fabricated using advanced zirconia-reinforced lithium disilicate (ALD) CAD/CAM glass-ceramic blocks. Materials and methods Using a standardized preparation protocol, three typodont molars were prepared to receive three different indirect overlay ceramic restoration designs. The typodont teeth were duplicated to get 27 resin dies that were randomly allocated into three groups (n = 9) based on the preparation design; group (O): a traditional overlay preparation with anatomical occlusal reduction, group (OS): anatomical occlusal reduction with circumferential shoulder finish line, and group (OG): anatomical occlusal reduction with a central groove preparation at the mid-occlusal surface. After standardized restorations fabricated following the manufacturer’s guidelines, the restorations were cemented to their corresponding dies and exposed to thermal aging corresponding to 6-month clinical service. Marginal gap was measured before and after thermal aging procedure using an optical microscope. To measure fracture resistance, specimens were loaded till failure using the universal testing machine. The Kruskal Wallis test was utilized to assess data among the groups, followed by Dunn’s post hoc test with Bonferroni correction. Differences in the marginal fit before and after thermal aging were evaluated using Wilcoxon Sign Rank test. Results A statistically significant difference in marginal fit was observed between the studied groups, with a p-value of 0.032 where group OS has the lowest micro gap compared to group OG and group O. The fracture resistance group (O) recorded the highest fracture resistance with a statistically significant difference between the studied groups at p value = 0.043. Conclusions Adjusting the tooth preparation significantly influenced both the fracture resistance load and the marginal fit observed for advanced zirconia-reinforced lithium disilicate glass-ceramic (ALD) overlays.